2004
DOI: 10.1096/fj.03-0962fje
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fusion of cells between species yields transdifferentiation and retroviral transfer in vivo

Abstract: Human cells can fuse with damaged or diseased somatic cells in vivo. Whether human cells fuse in vivo in the absence of disease and with cells of disparate species is unknown. Such a question is of current interest because blood exchanges between species through direct physical contact, via insect vectors or parasitism, are thought to underlie the transmission of zoonotic agents. In a model of human-pig chimerism, we show that some human hematopoietic stem cells engrafted in pigs contain both human and porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
(29 reference statements)
0
58
0
1
Order By: Relevance
“…As the duration of cell-cell co-incubation increases, small fusions might occasionally combine into larger ones, potentially resulting in a complete whole-cell fusion for certain cell types. This might explain the observations that stem cells can fuse with somatic cells after more than 10 days of co-culture in vitro (Cowan et al, 2005) or in vivo (Ogle et al, 2004;Ogle et al, 2005). Our data suggest that stem cells might start exchanging large cytosolic molecules or membrane proteins with somatic cells much earlier.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As the duration of cell-cell co-incubation increases, small fusions might occasionally combine into larger ones, potentially resulting in a complete whole-cell fusion for certain cell types. This might explain the observations that stem cells can fuse with somatic cells after more than 10 days of co-culture in vitro (Cowan et al, 2005) or in vivo (Ogle et al, 2004;Ogle et al, 2005). Our data suggest that stem cells might start exchanging large cytosolic molecules or membrane proteins with somatic cells much earlier.…”
Section: Discussionmentioning
confidence: 51%
“…Stem cells show a propensity of fusion with somatic cells (Cowan et al, 2005;Ogle et al, 2004;Ogle et al, 2005). To verify that cytoplasmic transfer between HUVECs and LVECs was not mediated by permanent cell fusion, we co-cultured LVECs with iHUVECs.…”
Section: Stem Cells Can Receive Large Cytoplasmic Macromoleculesmentioning
confidence: 99%
“…Fourteen injected swine from three separate litters were studied. Human cells were detected by reverse transcriptase (RT)-polymerase chain reaction (RT-PCR) for human b-2 microglobulin mRNA (Table 1) and by in situ hybridization for Alu (previously reported by Ogle et al 27 ) in peripheral blood and bone marrow of eight swine (approximately 60% of those injected). By both measures, the level of chimerism was greatest 1 week after birth (range 0.01-6%) and declined thereafter as determined by densitometry of RT-PCR bands relative to human:pig mixed controls (i.e., 1:1,1:10, 1:100, 1:1000, and 1:10,000) and by counting the number of Alu þ cells as a fraction of Alu À cells (average of 15 fields).…”
Section: Human Cell Detection In Swinementioning
confidence: 94%
“…Surveys of hundreds of human subjects who received a xenotransplants from swine have failed to document even one case in which that virus passed from swine to human [51][52][53][54] ; however, we recently found that porcine endogenous retrovirus can transfer when cells fuse and DNA is resorted. 27,55 Whether cell fusion can generate infectious retroviruses, however, is still not clear.…”
Section: Ogle Et Almentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described [18] in the 8 well chamber slides when the cells reached 50% confluency. Slides were washed with 1x PBS and placed in 100% acetone (cooled to 4°C) for 10 minutes.…”
Section: Cd73 Protein Expressionmentioning
confidence: 99%